A three-dimensional in vitro culture environment of a novel polymer scaffold, yielding chondroprogenitors and mesenchymal stem cells in human chondrocytes derived from osteoarthritis-affected cartilage tissue - Katoh, Shojiro; Yoshioka, Hiroshi; Iwasaki, Masaru; Senthilkumar, Rajappa; Rajmohan, Mathaiyan; Karthick, Ramalingam; Preethy, Senthilkumar; Abraham, Samuel JK (Journal of Orthopaedics, 2021)
We evaluated the expression of stem/progenitor biomarkers in osteoarthritic tissue derived chondrocytes cultured using a three-dimensional (3D) thermo-reversible gelation polymer (TGP). The chondrocytes from discarded biopsy tissues obtained from human elderly patients with osteoarthritis were cultured using the 3D-TGP up to six weeks. The chondrocytes grew in a tissue-like manner, without de-differentiation into fibroblasts, and the cells thus tissue-engineered were proven positive for CD49e, OCT4, CD-105 and STRO-1 by immunohistochemistry. This study establishes the efficacy of this 3D-TGP platform for clinically useable in-vitro tissue-engineered cartilage for improvising the clinical outcome of cell therapy for cartilage repair.